2018
DOI: 10.1097/scs.0000000000004064
|View full text |Cite
|
Sign up to set email alerts
|

The Distal Stump of the Intramuscular Motor Branch of the Obturator Nerve Is Useful for the Reconstruction of Long-Standing Facial Paralysis Using a Double-Powered Free Gracilis Muscle Flap Transfer

Abstract: Our experience suggests that the distal stump of the intramuscular motor branch of the obturator nerve may be useful for facial reanimation via double-powered free gracilis muscle flap transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…However, their technique was done on a small number of cases, only 6 and all were done in a single stage. 22 Our technique was completely different from the technique introduced by Biglioli and colleagues in which the masseteric nerve and CFNG were both done in a single stage with the masseteric nerve attached end to end with the obturator nerve, which meant motor fibers from the masseter arrived first followed by the CFNG in an end to side manner several months later. 11 The hypoglossal nerve is a good donor motor nerve for its strong impulse and a split segment can be mobilized to reach the nerve to gracilis directly.…”
Section: Discussionmentioning
confidence: 93%
“…However, their technique was done on a small number of cases, only 6 and all were done in a single stage. 22 Our technique was completely different from the technique introduced by Biglioli and colleagues in which the masseteric nerve and CFNG were both done in a single stage with the masseteric nerve attached end to end with the obturator nerve, which meant motor fibers from the masseter arrived first followed by the CFNG in an end to side manner several months later. 11 The hypoglossal nerve is a good donor motor nerve for its strong impulse and a split segment can be mobilized to reach the nerve to gracilis directly.…”
Section: Discussionmentioning
confidence: 93%
“…Eight studies scored 8 of 9 on the Newcastle-Ottawa scale, and 2 studies scored 7 of 9 on the scale, indicating all studies were of good quality. All studies lost a point in the comparability category because there were no controls and the studies were all retrospective, and 2 studies 13,24 lost another point in the selection category due to including both flaccid and nonflaccid paralysis patients in their study. Follow-up time ranged from 6 months for patients reanimated with MN, and 12 months for CFNG, to over 40 months.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Others have recommended using both a CFNG and the MN to provide both spontaneity and excursion. [12][13][14] Despite calls to standardize assessment of postoperative outcomes to allow better comparison between studies using validated measures, however, results continue to be reported in a heterogenous fashion with many different outcome measures used. 15,16 Recent additions such as the FACEgram software, 17 the FaCE instrument, 18 and the FACIAL CLIMA system 19 are objective, validated instruments, but because they are relatively new, they have not seen widespread use.…”
mentioning
confidence: 99%
“…According to a review by Boonipat et al, 16 the majority of dually innervated free gracilis muscle transfers performed by facial nerve specialists are done in a single staged fashion using end-to-end masseteric and end-to-side CFNG coaptations. Alternate neurorrhaphy patterns for gracilis innervation have also been described such as an end-to-end coaptation of the CFNG to obturator nerve and end-to-side coaptation of the masseteric nerve by Cardenas-Mejia et al 28 in a 2-stage procedure in 9 patients, and a double end-to-end coaption of the CFNG to the obturator and a masseteric nerve to the distal stump of the intramuscular motor branch of the gracilis muscle by Uehara et al 29 in 6 patients (Figure 3). Some experts have also attempted splitting the obturator nerve longitudinally to allow equal end-to-end inputs from both nerve coaptations.…”
Section: Dual Innervation Techniquesmentioning
confidence: 99%